Peningkatan Kemampuan Mengenal Angka Melalui Permainan Blok Angka Bergambar di RA Al-Qur’an Dina Padang Matinggi - Roma Diana; Kholidah Nur; Ali Masran Daulay (PT. Willy Print Art, 2024)
This study aims to improve the ability to recognize numbers in early childhood at RA Al-Qur “an Dina Padang Matinggi through the use of pictorial number block games. The formulation of the problem in this study includes three main aspects: improving children's number recognition skills using pictorial number block games. This research uses the Classroom Action Research (PTK) method with a cyclical approach involving several stages of intervention. The results of the research in the first cycle of 32 children who became research subjects, 12 children (37.5%) were in the category of developing very well, 7 children (21.87%) were in the category of developing as expected, 9 children (28.12%) began to develop, and 4 children (12.5%) had not developed. At the second meeting in the first cycle, there was a slight increase with 12 children (37.5%) in the category of developing very well, 8 children (25%) developing as expected, 8 children (25%) starting to develop, and 4 children (12.5%) still not developing. In the second cycle, the first meeting showed further improvement: 14 children (43.75%) were in the category of developing very well, 10 children (31.25%) were developing as expected, 6 children (18.75%) were starting to develop, and 2 children (6.25%) had not yet developed. The second meeting in the second cycle showed very significant results: 24 children (75%) are in the category of developing very well, 6 children (18.75%) are developing as expected, 1 child (3.12%) is starting to develop, and 1 child (3.12%) has not developed. These results indicate that the use of illustrated number block games gradually improves children's number recognition skills, especially after the second cycle.